IN VITRO ANTIBACTERIAL ACTIVITY AND PHYTOCHEMICAL ANALYSIS OF ORMOCARPUM COCHINCHINENSE EXTRACTS ON NOSOCOMIAL INFECTION CAUSING BACTERIA - Hepsibah A, Hannah; G, Jeya Jothi (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Objective: The present study was aimed at evaluating the antibacterial activity and phytochemical analysis of the leaf extracts of Ormocarpum cochinchinense. Methods: The leaf powder was extracted by sequential extraction method using chloroform, acetone, and methanol. Preliminary phytochemical analysis of the extracts was done using standard methods. The dried extracts were screened for antibacterial activity using disk diffusion method and the minimum inhibitory concentration (MIC) method. Results: The acetone extract showed the presence of flavonoids, tannins, steroids, phlobatannins, and saponins. Methanol extract contained flavonoids, tannins, phlobatannins, saponins, and terpenoids. The chloroform extract contained steroids. The chloroform extract did not show any activity, whereas the acetone extract showed significant activity against all the bacteria with a MIC value of 0.080 mg/ml against Escherichia coli (ATCC 25922) and Klebsiella pneumoniae (ATCC 15380) and 0.18 mg/ml against Staphylococcus aureus (meticillin resistant). The methanol extract showed very less activity. Conclusion: The present study has proved the antibacterial potency of O. cochinchinense for the first time. This plant is a potential source of antimicrobial agents of the future. Keywords: Antibacterial activity, Phytochemical analysis, Minimum inhibitory concentration, Ormocarpum cochinchinense, Acetone extract.